HUMOR AND SATIRE IN W. SHAKESPEARE'S COMEDIES - Erkinov Adham Anvar o'g'li (TADQIQOTLAR.UZ, 2024)
This article provides a comprehensive overview of the various forms of humor and satire found in William Shakespeare's comedies. It examines the significance of these elements in entertaining audiences, providing social commentary, and shaping the development of comedy as a literary and theatrical form. The article is supported by references to Shakespeare's original works and scholarly analyses of his comedic techniques.